Toxicity and cytopathology mediated by Bacillus thuringiensis in the midgut of Anticarsia gemmatalis (Lepidoptera: Noctuidae) - Castro, Bárbara Monteiro de Castro e; Martinez, Luis Carlos; Barbosa, Sergio Guedes; Serrão, José Eduardo; Wilcken, Carlos Frederico [UNESP]; Soares, Marcus Alvarenga; da Silva, Antonio Alberto; de Carvalho, Amélia Guimarães; Zanuncio, José Cola (Springer Nature, 2019)
Bioinsecticides and transgenic plants, based on Bacillus thuringiensis (Bt) toxins are important when managing Anticarsia gemmatalis Hübner (Lepidoptera: Noctuidae), a soybean defoliator pest. The interaction of these toxins with the caterpillar’s midgut cells determines their efficacy as an insecticide. The objective was to evaluate the toxicity of B. thuringiensis, subsp. kurstaki strain HD-1 and cytopathological changes mediated by these bacterial toxins in the midgut of A. gemmatalis caterpillars. Insecticidal efficacy was determined by calculating lethal concentration values (LC 25 , LC 50 , LC 75 , LC 90 and LC 99 ) in the laboratory. Midgut fragments from A. gemmatalis were extracted after bacterial ingestion and evaluated by light, transmission electron and confocal microscopy. The Bt median lethal concentrations showed toxicity [LC 50 = 0.46 (0.43–0.49) mg mL −1 ] to fourth instar A. gemmatalis caterpillars after 108 hours. Bt induces severe cytotoxicity to A. gemmatalis midgut epithelial cells with increasing exposure over time, causing cellular disorganization, microvillus degeneration, cell fragmentation and protrusion, peritrophic membrane rupture, and cell vacuolization. The cell nuclei presented condensed chromatin and an increase in lysosome numbers. Apoptosis occurred in the midgut cells of caterpillars exposed to Bt. A regenerative response in A. gemmatalis caterpillars was observed 8 hours after exposure to Bt, however this response was not continuous. Toxins produced by Bt are harmful to A. gemmatalis at median concentration with structural damage and death of the midgut epithelial cells of this insect.